Ferroportin is transcriptionally upregulated by oxldl through Nrf2 and is counteracted by LPS/IFNγ in murine macrophages - Marques, Liliana (2014)
This work was supported by National Institute of Health Dr Ricardo Jorge, I.P, INSERM (Institut National de la Santé et de la Recherche Médicale), CNRS (Centre National de la Recherche Scientifique), ANR (Agence Nationale de la Recherche, France; ANR- 08-GENO-000) , Fundação para a Ciência e Tecnologia (Grant SFRH/BD/48671/2008) and BioFIG (Center for Biodiversity, Functional and Integrative Genomics). The authors report no conflit of interests.